Relación entre la competitividad turística y el crecimiento económico departamental: Colombia 2015-2018 (2020)
This paper analyzes the relationship between tourism competitiveness and economic growth in Colombia. The methodology was applied to 31 departments of Colombia and Bogotá D.C. for the 2015-2018 period, using a linear regression model by Ordinary Least Squares, with the growth of departmental tourism GDP as the response variable and six of the eight criteria of the Regional Tourism Competitiveness Index of Colombia as explanatory variables. In general, the analysis showed that the Business, Infrastructure and Destination Management criteria explain, with great statistical significance, the growth of the departments tourism GDP; while the Cultural and Social criteria do so with a lower level of confidence. The Environmental criterion, on the contrary, does not explain the departmental economic growth. Together, the tourism competitiveness criteria explain 77% of the variability of tourism GDP. The study concludes that the conditions and tools for the creation and formalization of a business in the tourism sector must be improved, the development of tourism projects must be strengthened through public-private partnerships, and investment in infrastructure must be stimulated, especially in emerging destinations.